Design and analysis of a configuration-based lengthwise morphing structure. (May 2020) - Wang, Jieyu; Zhao, Yinjun; Xi, Fengfeng; Tian, Yingzhong
Abstract: The ability of changing aircraft wing shape or geometry has drawn great attention of researchers in the past decades. This paper proposes a new approach to design a lengthwise morphing structure for an airfoil morphing wing. The structure is composed of n planar mechanism units. Each unit is designed to have 3 degrees-of-freedom (DOFs) that can be fully controlled by two actuators using lockable joints. This structure is reconfigurable through dual mode switching by locking specific joints. The end-effector of the mechanism can reach any desired position and the morphing wing can change to any desired shape. When locking three or four actuators, the structure turns into a statically determinate or indeterminate truss structure to withstand required loads. Force analysis for the structure during morphing motions is conducted based on statics, and an optimization method is used to determine the appropriate number of actuators and their placements. Prototypes with or without skins are fabricated to verify the feasibility of the design.